Oil and Gas Investments in Iraq and Challenges of Sustainable Development Strategies - Zghair, Aqeel Kareem (Journal of Legal and Political Studies, 2026)
In 2009, the oil and gas sector in Iraq witnessed a critical turning point with the implementation of licensing contracts, which encouraged unprecedented foreign investment in the sector. This resulted in rapid economic growth and noticeable improvement. Consequently, the federal government and the Kurdistan Regional Government sought to increase oil and gas production, which impacted revenue flows for companies and the state. Despite , serious environmental and social challenges emerged due to the increased production, such as climate change, resource depletion, and environmental degradation. As an important party in this transformative progress, the Kurdistan Region plays a vital role in shaping the future of the country's sustainable development. Aware of these challenges and the legislative shortcomings in Iraq, this research aims to identify the key challenges and provide a comprehensive understanding of sustainable development strategies in the oil and gas sector, with the goal of exploring effective solutions to mitigate these challenges and facilitate informed decision-making and the implementation of appropriate strategies. Keywords: Sustainable development, investment, oil and gas sector, sustainability challenges.
Keywords: Sustainable development; investment; oil and gas sector; sustainability challenges